2017
DOI: 10.1080/09168451.2016.1240605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of super-hard rice bread blended with black rice bran on amyloid β peptide production and abrupt increase in postprandial blood glucose levels in mice

Abstract: Alzheimer's disease and type 2 diabetes are very serious diseases with the latter having been suggested to cause the former. We prepared super-hard rice bread blended with black rice bran (SRBBB), which contained a high amount of resistant starch that showed strong inhibitory activities against β-secretase and acetylcholinesterase even after heating. Black rice bran showed greater β-secretase inhibitory activity (3.6-fold) than Koshihikari rice. The bran contained more oleic acid and anthocyanin, meaning that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…And after cooking, only HPT KO showed BACE1 inhibitory activity (12.0%) although Koshihikari polished rice did not show BACE1 inhibitory activity. These results indicate that the BACE1 inhibitory activity of pigmented rice bran is much stronger than that of ordinary rice bran, as we reported in our previous paper [12] . Physical properties of cooked rice: As shown in Table 2, the physical properties of cooked rice were measured in bulk using a Tensipresser.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…And after cooking, only HPT KO showed BACE1 inhibitory activity (12.0%) although Koshihikari polished rice did not show BACE1 inhibitory activity. These results indicate that the BACE1 inhibitory activity of pigmented rice bran is much stronger than that of ordinary rice bran, as we reported in our previous paper [12] . Physical properties of cooked rice: As shown in Table 2, the physical properties of cooked rice were measured in bulk using a Tensipresser.…”
Section: Resultssupporting
confidence: 86%
“…Positive health effects from these pigments in the bran layer of rice have been reported; red and black rice decreased atherosclerotic plaque formation and increased the antioxidant status in rabbits due to an enhanced serum high-density lipoprotein cholesterol and apolipoprotein A1 concentration [11] . We prepared super-hard rice bread blended with black rice bran, which contained a high amount of RS, and demonstrated its strong inhibitory activity against β-secretase (BACE1) and acetylcholinesterase even after heating [12] .…”
Section: Introductionmentioning
confidence: 99%
“…BR extract is also rich in polyphenols with anthocyanins, which have no toxic effects at doses ≤20 mg/kg/day in rat and 25 mg/kg/day in mice (43). Previous studies have reported that bread containing BR contributes to the reduction of Aβ peptide concentrations in the plasma of aged mice (44). In addition, BR and its constituent, cyanidin, have been shown to attenuate Aβ-induced neuronal cell death via modulation of the mitochondrial death pathway in SK-N-SH cells (45).…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, we found that a super-hard rice bread blended with black rice bran (SRBBB), which contained a high amount of resistant starch (RS), provided a strong inhibitory activity against β-secretase (BACE1) and acetylcholinesterase, even after heating. Furthermore, aged mice fed the SRBBB diet for 4 weeks showed lower amyloid β40 peptide in their blood than mice fed a commercial feed diet [38].…”
Section: Introductionmentioning
confidence: 92%